Evaluation of yeast-based additives on rumen fermentation in high- and low-concentrate diets using a dual-flow continuous culture system - Cagliari, Amanda Regina (2024)
The objective of this study was to evaluate the efficacy of using 3 yeast-based additives as an alternative to sodium monensin on rumen fermentation parameters using a dual-flow continuous fermentation system. Ten fermenters (1,223 ± 21 mL) were used in 2 simultaneous 5 × 5 Latin squares arrangement with 3 periods of 10 d each, with 7 d for diet adaptation and 3 d for sample collections. Each Latin square assigning either a low or high level of concentrate to beef cattle diets, with 5 specified treatments: Control: no additives; Blend 1: yeast culture (Saccharomyces cerevisiae), beta-glucans, fructooligosaccharides, galactooligosaccharides, and mannanoligosaccharides [1,600 mg/kg dry matter (DM)]; Blend 2: Beta-glucan and mannanoligosaccharide fractions from S. cerevisiae (1,600 mg/kg DM); Yeast Cells: hydrolyzed, inactivated, and spray-dried yeast cells (S. cerevisiae; 2,133 mg/kg DM); monensin (25 mg/kg DM). On days 8, 9, and 10, samples of 500 mL of solid and liquid digesta effluent were mixed, homogenized, and stored at -20 °C. Subsamples of 10 mL were collected for later determination of ammonia nitrogen (NH3-N) and volatile fatty acids (VFA). Diets with high-concentrate showed higher organic matter (OM) digestibility but lower crude protein and neutral detergent fiber (NDF) digestibilities (P < 0.01). There were no feed additive effects for DM, OM, and NDF digestibilities (P > 0.05). Total VFA concentration and butyrate concentration were higher for the high-concentrate diet (P < 0.01). Conversely, pH and concentrations of acetate and iso-butyrate were higher for the low-concentrate diet (P < 0.01). Treatments with Blend 1, Blend 2, and Yeast Cells had higher VFA concentrations compared to the control (P = 0.04). Blend 1 treatment exhibited higher propionate concentration in fermenters fed with a high-concentrate diet (P < 0.01). In the high-concentrate diet, Blend 1 had a lower acetate: propionate ratio compared to Control, Yeast Cells, and Blend 2 treatments (P < 0.01). The high-concentrate diet showed higher means for all other parameters: Microbial efficiency, N efficiency, N flow, and Bacterial N flow (P < 0.01). Treatments with Blend 2 and Control showed higher rumen undegradable protein N flow compared to Yeast Cells and Blend 1 treatments (P < 0.01). Our findings imply that yeast-based additives might be used as alternatives to monensin, improving ruminal fermentation and promoting enhanced sustainability in livestock.